Ответ(ы) на вопрос:
[latex] \frac{1}{x+d} + \frac{3xd}{x^3+d^3} = \frac{1}{x+d} + \frac{3xd}{(x+d)(x^2-xd+d^2)} =[/latex]
[latex]= \frac{1*(x^2-xd+d^2)}{(x+d)*(x^2-xd+d^2)} + \frac{3xd}{(x+d)(x^2-xd+d^2)} = \frac{1*(x^2-xd+d^2)+3xd}{(x+d)*(x^2-xd+d^2)}=[/latex]
[latex]= \frac{x^2-xd+3xd+d^2}{(x+d)*(x^2-xd+d^2)}=\frac{x^2+2xd+d^2}{(x+d)*(x^2-xd+d^2)}=\frac{(x+d)^2}{(x+d)*(x^2-xd+d^2)}=[/latex]
[latex]=\frac{(x+d)*(x+d)}{(x+d)*(x^2-xd+d^2)}=\frac{x+d}{x^2-xd+d^2}[/latex]
Ответ: [latex]\frac{x+d}{x^2-xd+d^2}[/latex]
Не нашли ответ?
Похожие вопросы